Analysis of Cutting Forces during Machining with Additive-Produced Milling Head - Slabejova, Silvia; Sajgalik, Michal; Timko, Pavol; Kozovy, Peter; Novak, Martin; Cedzo, Miroslav (Manufacturing Technology Journal, 2023)
Today's milling cutting tools are produced in various types and shapes for a wide variety of machining processes. Development continues and offers new technological solutions. The design of replaceable milling heads offers a significant cost reduction, as only the worn-out part is replaced instead of the en-tire tool. The tough connection between the tool and the shank achieves stable performance in roughing and finishing milling. Because of the possibility of using different milling inserts, the number of neces-sary tools will also be reduced and the flexibility of using milling tools will increase. The article exam-ines the cutting forces when machining a milling head produced by additive technology and made of Onyx material, which is reinforced with carbon fibre.
Keywords: Cutting Forces; Milling Head; Additive Production